Cause and risk factors for readmissions after transcatheter aortic valve replacement. (25th November 2020) - Arora, S; Strassle, P.D; Hendrickson, M.J; Sitammagari, K; Qamar, A; McRee, C; Yeung, M; Vavalle, J.P
Abstract: Background: Hospital readmissions following transcatheter aortic valve replacement (TAVR) are associated with higher costs and worse outcomes. Purpose: Identify causes and risk factors for readmissions after TAVR Methods: Hospitalizations of adults aged ≥50, with aortic stenosis and undergoing elective TAVR between 2012 and 2016 in the National Readmission Database were analyzed. Multivariable generalized logistic regression, adjusting for age, sex, Charleson Comorbidity Index, primary insurance type, median household income, hospital type and size, were used to assess the effect of inpatient complications, length of stay (LOS), discharge disposition, and TAVR hospital volume on 30-day cardiovascular (CV) and non-cardiovascular (non-CV) readmission. Results: Between January 2012 and November 2016, 56, 858 weighted TAVR hospitalizations were included. The most common causes of readmissions after TAVR were heart failure (23%), infection (17%), gastrointestinal (11%), respiratory (8%), and "other" non-CV causes (8%). The adjusted odds of both CV and non-CV readmissions were significantly higher in patients with acute kidney injury, inpatient LOS ≥5 days, those discharged to skilled nursing facility (SNF) and those treated at medium volume compared with high volume hospitals, Table 1. Conclusion: Heart failure is the most common cause of readmissions after TAVR. Inpatient incidence of acute kidney injury, as well as longer LOS, SNF discharge and lower hospital TAVR volume were associated with higher odds of 30-day readmissions. Funding Acknowledgement: Type of funding source: None